Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1109/tdei.2015.004731
|View full text |Cite
|
Sign up to set email alerts
|

Neural network approach to separate aging and moisture from the dielectric response of oil impregnated paper insulation

Abstract: This paper presents a study of the impact of two important parameters, moisture and aging of the oil/paper dielectric used as insulation in power transformers.The way in which these two parameters influence different parameters of the Frequency Domain Spectroscopy (FDS) measurements, is emphasized.Different FDS parameters were measured by varying the moisturecontent and the aging degree of the oil impregnated paper.The use of two types of neural networks for analysis of the results was necessary in order to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Hadjadj et al [131] reported the feasibility of using poles to get rid of/encompass equipment volume effect. Attempts to separate moisture and aging have been reported in the last decades [131][132][133][134].…”
Section: Frequency Domain Spectroscopymentioning
confidence: 99%
“…Hadjadj et al [131] reported the feasibility of using poles to get rid of/encompass equipment volume effect. Attempts to separate moisture and aging have been reported in the last decades [131][132][133][134].…”
Section: Frequency Domain Spectroscopymentioning
confidence: 99%
“…Many studies [3,6,7,11,12] have been published on the subject of separating aging and moisture from FDS results. These studies, which contributed to the development of the FDS technique, are used in diagnosing the insulation conditions of field power transformers.…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be emphasized that moisture and aging separation still constitute a challenging point in this domain [6,34,35].…”
Section: Moisture In Oil Determinationmentioning
confidence: 99%